2017
DOI: 10.1080/2162402x.2017.1353857
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade at the time of tumor escape potentiates the immune-mediated antitumor effects of a melanoma-targeting monoclonal antibody

Abstract: Tumor antigen-targeting monoclonal antibodies (TA-targeting mAbs) are used as therapeutics in many malignancies and their capacity to mobilize the host immunity puts them at the forefront of anti-cancer immunotherapies. Both innate and adaptive immune cells have been associated with the therapeutic activity of such antibodies, but tumor escape from mAb-induced tumor immune surveillance remains one of the main clinical issues. In this preclinical study, we grafted immunocompetent and immunocompromised mice with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
3
9
0
1
Order By: Relevance
“…In fact, TRIMELVax/anti-PD-1 combination generated only marginal enhancing of TRIMELVax efficiency, although long-term effects in tumor-bearing animals cannot be discarded. In our model, treatment of tumor-bearing mice with anti-PD-1 alone induced tumor growth retardation, but did not have a significant impact on the overall survival, in line with other observations, 40 41 which can be explained by acquired resistance to anti-PD-1/PDL1 therapies described in both mouse models and clinical trials. 3 42 43 …”
Section: Discussion/conclusionsupporting
confidence: 91%
“…In fact, TRIMELVax/anti-PD-1 combination generated only marginal enhancing of TRIMELVax efficiency, although long-term effects in tumor-bearing animals cannot be discarded. In our model, treatment of tumor-bearing mice with anti-PD-1 alone induced tumor growth retardation, but did not have a significant impact on the overall survival, in line with other observations, 40 41 which can be explained by acquired resistance to anti-PD-1/PDL1 therapies described in both mouse models and clinical trials. 3 42 43 …”
Section: Discussion/conclusionsupporting
confidence: 91%
“…They demonstrated that anti-PD-1 treatment of mice, at the time of tumor emergence, restored the effector functions of T cells, NK cells, and γδ T cells, leading to the inhibition of tumor progression and extension of survival. These data confirmed that combination of checkpoint blockade and immunotherapy may represent a promising approach for melanoma patients [ 81 ].…”
Section: Malignant Melanomasupporting
confidence: 69%
“…Three-µm thin sections of formalin-fixed paraffin-embedded tissues were mounted on Flex microscope slides (Dako) and allowed to dry overnight at room temperature before immunohistochemistry processing, as previously described [63]. Briefly, PT-Link ® system (Dako) was used for pre-treatment.…”
Section: Methodsmentioning
confidence: 99%